Pro-defence activities of women’s organisations during the wars for independence and the establishment of the Polish borders in the years 1914–1921 - Kurcewicz, Urszula (Before the Battle, 2023)
The aim of the study is to show the levels on which Polish women joined the endeavour to regain independence after the period of the Partitions. Principally, the study covers the time period from 1914 to the end of the Polish–Bolshevik War in 1921. However, in order to fully present the background of the pro-defence activities of Polish women, the text also refers to a number of events from the period preceding the outbreak of World War I. The activity of female combatants in the struggle for independence and establishment of national borders during the Second Polish Republic is also discussed. The text consists of two parts: in the first part, the author presents the participation of women in paramilitary organisations and armed struggle during World War I and their participation in the Greater Poland Uprising and in the battles for Lviv in Eastern Galicia. She also discusses the activities of women in the Legions, the Polish Military Organisation, and the Voluntary Legion of Women. The second part of the study presents the contribution of civilian women's organisations, in particular the Polish White Cross, to help soldiers and civilians injured in combat. The author points to the role played by the Women’s League for War Alert and the League of Women of Galicia and Cieszyn Silesia in securing the army's material base. Faced with the threat of the Bolshevik invasion, women not only actively supported the combatants, but also created a resilient defence propaganda machine in dozens of magazines. The author discusses the agitation campaign for joining the Volunteer Army. The activists of women's associations organised lotteries, festivities, and competitions, during which they raised funds to support the fighters. The sources of the paper are memoirs and the relevant period press, as well as contemporary monographs and scientific articles.